Biochemical, Microbiological and Organoleptic Properties of Probiotic Pineapple Juice Developed by Lactic Acid Bacteria - Hossain, M. A.; Hoque, M. M.; Hossain, M. M.; Kabir, M. H.; Yasin, M.; Islam, M. A. (Journal of Scientific Research, 2020)
An experiment was undertaken to determine the suitability of pineapple juices as raw materials for the production of fermented probiotic juice by two lactic acid bacteria, Lactobacillus plantarum and Lactobacillus fermentum. Three probiotic juice samples inoculated with L. plantarum (S-2), L. fermentum (S-3) and with both L. plantarum and L. fermentum (S-4) were compared with that of control sample (S-1) where no Lactobacillus strains were used. Fermentation was carried out at 37 °C for 48 h. Then the juice samples were stored at 4 °C and studied the change in their physicochemical properties at day 0, 7, 14 and 21. Both L. plantarum and L. fermentum were able to withstand and utilize fruit juices for their cell synthesis as indicated by a decrease in fruit sugar and an increase in acidity. Although the lactic cultures in fermented probiotic juices gradually lost their viability, the viable cell counts of these strains remained at 107 CFU/100 mL after 14 days in cold storage. From sensory evaluation, the juice sample prepared with L. plantarum exhibits the best result during storage time. Hence, pineapple juice might be used as a suitable medium for the production of a healthy probiotic beverage.